MOOD OF THE DOCTORS: PROBLEMS, CHALLENGES AND PERSPECTIVES OF AI USE IN MEDICINE - Tudor Florin Ursuleanu; Alina Ionela Calin; Maria Paula Comanescu; Hlescu Cristian Stefan; Roxana Grigorovici; Andreea Roxana Luca; Ramona Elena Teiu; Alexandru Grigorovici (Romanian Journal of Oral Rehabilitation)
Aim of the study: Artificial intelligence (AI) is gaining increasing and obvious implications in medical practice. The novelty of the research paper consists in evaluating the implicative relationship doctor-artificial intelligence (AI) in medical practice, a hot and current topic, with implications on physicians’ receptivity to the use and perspectives of AI in medicine, which derive from the mood, introverted and extroverted components of physicians. Materials and methods: The aim of the research is to reveal the challenges and prospects of using AI in medicine in relation to the mood of doctors, namely, the classification of emotions, feelings as part of the introvert and attitude, as the extrovert part of doctors, in practical interaction with AI. This includes providing an aesthetic and ethical experience in the doctor-AI relationship within medical practice. .Results: The holistic approach to the doctor-patient-AI relationship is identified as a solution for increasing the attention and involvement of doctors in the use of high-performance technologies. This approach supports medical practice outcomes and aims to improve the quality of life of patients. Conclusions: The findings suggest that enhancing the doctor-AI relationship through a focus on emotions and attitudes fosters receptivity among physicians, leading to better integration of AI technologies and improved patient care.